Mechanical properties and microstructure analysis of mild steel welding made by GTAW / Saleh Suliman Saleh Elfallah - Saleh Elfallah, Saleh Suliman (UiTM Press, 2024)
This work discusses the effect of gas tungsten arc welding (GTAW) variables on the welding transverse tensile strength and hardness of S 235JR at different groove configurations. The welding microstructure and numerical fracture mechanism are also discussed. GTAW is increasingly emerging in the local industry due to its advantages over conventional shielded metal arc welding (SMAW). The properties of steel welding have always concerned manufacturers and researchers. Since steel structures experience forces such as tensile, it’s vital that good welding has increased tensile strength. It was reported that the hardness of welding affects the welding properties and, therefore, the integration of welded structures. The groove shape of the joining ends determines the size of the FZ and affects the dilution; thus, it is important to study the groove shape due to its effect on the final properties of welding.